Pengaruh Penggunaan ChatGPT dan Manajemen Waktu terhadap Efisiensi Belajar Mahasiswa Pendidikan Administrasi Perkantoran - Ainayya, Alika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study examines the impact of ChatGPT technology and time management on the learning efficiency of students in the Office Administration Education Study Program at Universitas Negeri Jakarta. A descriptive research approach was used, using a purposively selected sample of 38 students. Data were collected through a survey and analyzed using multiple linear regression. The results showed that the use of ChatGPT and time management significantly influenced learning efficiency, both independently and simultaneously. The use of ChatGPT showed a more significant influence than time management. The integration of the two markedly improved students' academic efficiency by facilitating access to information, understanding of ideas, and organization of study schedules. This study highlights the importance of incorporating AI technologies in education while enhancing time management skills to foster a more effective and efficient learning experience.